Evaluating electronic medical record implementation using the HOT-FIT model at UPTD Puskesmas Ungaran - Kurniawati, Novi Ika; Widiyanto, Wahyu Wijaya (Institute of Computer Science (IOCS), 2025)
This study evaluated the implementation of Electronic Medical Records (EMR) at UPTD Puskesmas Ungaran using the Human-Organization-Technology Fit (HOT-FIT) model. The research employed a descriptive qualitative approach to explore how human readiness, organizational support, and technological infrastructure influenced EMR adoption. Data were collected through in-depth interviews, observations, and document analysis involving twelve healthcare professionals. Thematic analysis revealed that most users had limited training and lacked confidence in using the system, often leading to partial documentation. Organizationally, there was minimal supervision, unclear standard operating procedures, and no internal technical support. Technologically, the system frequently experienced downtime and integration failures with national platforms such as Pcare BPJS. These findings indicate that the EMR implementation remains fragmented and procedural, rather than transformative. The study concluded that the success of EMR adoption requires not only system availability but also holistic readiness across all HOT-FIT dimensions. Practical recommendations include ongoing capacity-building, improved policy enforcement, and user-centered system development. This study provides insight for policymakers and healthcare managers to enhance EMR sustainability in primary care settings.